INOVASI TERHADAP MODEL PEMBERDAYAAN KELOMPOK PETERNAK SAPI DI DESA SUKA MULYA KECAMATAN BANGKINANG - Riska Aulya Rahmadhina; Raja Muhammad Amin; Rury Febrina (JURNAL TRIAS POLITIKA, 2023)
ABSTRACTThis study aims to determine the form of community empowerment in Suka Mulya Village through human development, business development, and environmental development, in the process of community empowerment and village government innovations on the community empowerment model of Suka Mulya Village, Bangkinang District. The method used in this research is to use a qualitative approach with data collection techniques namely interviews. The results of this study are the form of an innovative model for empowering cattle farmer groups in Suka Mulya Village including human development, namely by coaching through a corn-cow integration system program with the aim of optimally utilizing the potential of natural resources. For business development, namely with business training in making herbal herbs for cows. This aims to be a new innovation in increasing the entrepreneurial spirit of cattle farmers. The next step is to develop the environment, namely by training and fostering the utilization of cow dung waste into biogas. Finally, institutional development namely the role of Kampar district plantation and livestock service as a forum for information strengthening cattle breeder empowerment activities. Suggestions from this study are that it would be better to give a form of empowerment innovation that is more technology-based so that the cattle farmer groups become more empowered and develop, so that the goals of community empowerment can be realized properly.ABSTRAKTujuan penelitian ini ialah guna mengetahui bentuk dari pemberdayaan masyarakat desa Suka Mulya melalui bina manusia, bina usaha, dan bina lingkungan, dalam proses pemberdayaan masyarakat serta inovasi pemerintah desa terhadap model pemberdayaan masyarakat Desa Suka Mulya, Kecamatan Bangkinang. Penelitian ini menggunakan metode pendekatan kualitatif dengan teknik pengumpulan data yakni wawancara. Hasil dari penelitian ini ialah bentuk dari inovasi model pemberdayaan kelompok peternak sapi di Desa Suka Mulya meliputi bina manusia yakni dengan pembinaan melalui program sistem integrasi jagung-sapi dengan tujuan memanfaatkan potensi sumberdaya alam dengan optimal. Untuk bina usaha yakni dengan pelatihan usaha pembuatan jamu herbal untuk sapi. Ini bertujuan agar menjadi inovasi baru dalam peningkatan jiwa wirausaha dari peternak sapi. Selanjutnya bina lingkungan yakni dengan pelatihan dan pembinaan pemanfaatan limbah kotoran sapi menjadi biogas. Terakhir, bina kelembagaan, yakni dengan adanya peran dari Dinas Perkebunan dan Peternakan Kabupaten Kampar sebagai wadah informasi dalam penguatan kegiatan pemberdayaan peternak sapi. Saran dari penelitian ini yaitu alangkah baiknya diberikan bentuk inovasi pemberdayaan yang lebih berbasis pada teknologi agar para kelompok peternak sapi menjadi lebih berdaya dan berkembang, sehingga tujuan dari pemberdayaan masyarakat dapat terwujud dengan baik.